Defining curricular priorities for student-as-teacher programs: A National Delphi Study. (4th March 2018) - Rana, Jasmine; Sullivan, Amy; Brett, Molly; Weinstein, Amy R.; Atkins, Katharyn M.; ,
Abstract: Background: "Student-as-Teacher" (SaT) programs have been growing in number to prepare medical students for their teaching roles in residency and beyond, but it remains unknown what content areas should be covered in SaT curricula. Aim: To determine five to ten "essential" content areas for inclusion in SaT curricula using expert opinion. Methods: Using a three-round Delphi process, moderators iteratively surveyed a panel of 28 medical educators (25 academy directors and three individuals identified as having expertise in undergraduate medical education) representing 25 medical schools in the United States. This "SaT Delphi Working Group" was tasked with rating topics for inclusion in SaT curricula on a 3-point scale (i.e. 1. "essential, " 2. "important, but not essential" 3. "not important"). Topics achieving ≥70% consensus as "essential, " "important" or "not important" were accepted by the moderators and removed from subsequent rounds. Results: Hundred per cent response rate ( n = 28) was achieved for all survey rounds. Five content areas reached consensus as "essential" for inclusion in a SaT curriculum: feedback, bedside teaching and clinical precepting, small-group teaching, case-based teaching and professionalism as a medical educator. Conclusion: This consensus from a group of leaders in medical education is a first step toward the implementation of more developmentally-appropriate SaT competencies.